Comparative study of residential roof truss construction methods: prefabrication and built onsite - Mohd Sani, Mohd Syahrul Hisyam; Muftah, Fadhluhartini (2009)
This paper reports a comparative study of two types of residential roof truss method (prefabrication method and built onsite method) in Malaysia. The first light and easy frame trusses were constructed on site using nailed plywood gusset plates. These trusses presented acceptable spans but demanded considerable time to build. In the 1950's the metal connector plate changed the truss industry by allowing efficient prefabrication of short and long span trusses. With the growing demand for affordable housing, increasing construction costs and sensitive concern for energy-efficiency, contractors and builders across Malaysia have recently begun to re-examine their options for the delivery of housing. Both prefabricated roof truss methods and onsite roof truss construction method are used currently. From these two methods, many macroeconomic factors and regulatory factors like speed of construction and use advanced technology have been cited as reasons for this; little attention has been paid to the nature of the residential construction industry, its operational structures and the ability of the product itself to accommodate the contractor's needs and preferences. From these two methods, the site observation, interview and questionnaire data are been analysed from the characteristic factors that involve in roof truss construction. All the parties that involve in construction industry like roof truss manufacturers, contractors and consultants are being interviewed and asked about the roof truss methods. Finally the result that been generated is show that the prefabricated method is the most popular method and give many advantages to Malaysian construction industry.